الملامح الإسلامية في شعر شاعر الرسول عبدالله بن رواحة: دراسة وصفية تحليلية: The Islamic features in the poetry of the Prophet’s Poet Abdullah bin Rawahah:a descriptive and analytical studay - Hafiz Muhammad Umar Farooq; Prof. Dr. Khursheed-ul-Hasan Rizvi (AL-IDRAK JOURNAL, 2023)
Abdullah bin rawaha (RA) is one of the most famous Prophet's poets and one of the poets of the early days of Islam. He belongs to the class of veteran poets. He is a poet; his poetry flowed with admirable fluency and strength. Every since his islam he devoted his poetic genius to it service. This research aims to investigate the Islamic features that emerged in the poetry of the Prophet's poet Abdullah bin Rawahah, and some of them are the features of faith, morality and emotional ; which are among the most important features to be taken into consideration by the Muslim in all his positions and actions. The research follows the analytical descriptive approach and focuses on highlighting the impact of the Quran Karim and the Sunnah of the Great Prophet and focuses on the Islamic features of faith and ethics from the poet. The research concluded that the poet provided a significant consideration to several Islamic features and gave them evident care and obvious attention. The study showed that the poet was influenced by islam in those features he took care about, and that can be seen and observed in his right and straight dealing with human life and religion from the Islamic perspective. And the research ends with the most important result which we found.